How people's food disgust sensitivity shapes their eating and food behaviour. (1st August 2018) - Egolf, Aisha; Siegrist, Michael; Hartmann, Christina
Abstract: Although research regarding disgust has increased enormously in the last decades, to date there is a lack of published research about the influence of food disgust on various food-related behaviours. Our study aimed to provide an understanding about the relationships between food disgust sensitivity and eating preferences (texture-based food rejection), habits (variety seeking), and behaviours (picky eating) as well as food waste frequency. Additionally, sociodemographic characteristics associated with food disgust sensitivity were examined. German-speaking Swiss adults ( N = 1181) completed a paper-and-pencil questionnaire. Next to the Food Disgust Scale (FDS), the questionnaire included several established eating behaviour scales, such as the Adult Picky Eating Questionnaire, a scale regarding seeking food variety and a food frequency questionnaire. In addition, food waste frequency was also assessed by self-report. Multiple regression analyses showed that with increasing age, food disgust sensitivity scores increased and women showed higher FDS scores than men. Moreover, while picky eating and the rejection of certain food textures were both positively associated with higher FDS scores, seeking variety in foods was negatively associated with food disgust sensitivity. Significant correlations between FDS scores and the frequency of consuming certain foods were observed (e.g. vegetables, seafood). Finally, people with higher FDS scores reported a higher frequency of wasting food than people with lower FDS scores. The results indicate that individual food disgust sensitivity plays a role in various food domains.